A novel radioimmunoassay of allopregnanolone - Bicíková, M; Lapcík, O; Hampl, R; Stárka, L; Knuppen, R; Haupt, O; Dibbelt, L (Steroids, 1995)
A radioimmunoassay for determination of 3 alpha-hydroxy-5 alpha-pregnan-20-one (allopregnanolone) in serum or plasma has been developed and evaluated. The method employs rabbit antiserum to 3 alpha-hydroxy-5 alpha-pregnane-11,20-dione-11-O-carboxymethyloxime bovine serum-albumin conjugate and tritiated radioligand. The main cross-reactant interfering in the assay, progesterone, is eliminated by permanganate oxidation. Two assay variants were compared, with and without a micro-column chromatography. The simplified variant appeared to be reliable enough for determination of allopregnanolone in normally menstruating women at luteal phase, whereas the column-chromatography step is necessary when analyzing samples of expected low analyte concentration as in women in follicular phase, postmenopausal women, or in men. The levels of allopregnanolone in healthy women correlated excellently with progesterone in agreement with previous findings.
Keywords: referenční hodnoty; Chromatography, Liquid; senzitivita a specificita; Sensitivity and Specificity; Humans; Antibody Specificity; oxidace-redukce; Female; Potassium Permanganate; Progesterone; lidé; Radioimmunoassay; radioimunoanalýza; pregnanolon; reprodukovatelnost výsledků; ženské pohlaví; chromatografie kapalinová; Reproducibility of Results; specificita protilátek; progesteron; Oxidation-Reduction; Reference Values; manganistan draselný; Pregnanolone